The paradox of productivity: agricultural productivity promotes food system inefficiency. (2019) - Benton, Tim G.; Bailey, Rob
Non-technical summary: The principal policy focus for food has been to increase agricultural productivity and to liberalize markets allowing globalized trade. This focus has led to huge growth in the supply of agricultural produce, more calories becoming available, and price declining. The availability of cheaper calories increasingly underpins diets creating malnourishment through obesity, and global competition incentivizes producers who can produce the most, cheaply, typically with environmental damage. We propose re-focusing, away from yields per unit input, to the food system's overall productivity and efficiency – the number of people that can be fed healthily and sustainably per unit input. Technical summary: Since the Second World War, and particularly in recent decades, the over-arching rationale of agricultural and food trade policy has been that by increasing the productivity of agriculture and efficiency of its markets, trade will drive down food prices, drive up choices and food availability: implicitly defining more available and cheaper food as the route to achieving the international public good of global food security. Here we hypothesize that a focus on increasing availability of food, and lowering food prices through focusing on agricultural productivity and trade does reduce prices and increases availability, but also encourages the externalization of costs on health and environment, and instead of providing public goods arguably represents market failure. In other words, a focus on increasing agricultural yields and efficiency decreases the efficiency of the food system through incentivizing externalization of costs. The focus should rather be on the efficiency of the food system to deliver profits, healthy diets and a healthy planet. Reframing the productivity argument towards the efficiency of the food system provides a clear route to reducing market failure, improving public health and sustainability.